2011
DOI: 10.14710/jitaa.36.1.27-35
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Farmers’ Decision to Increase Beef Cattle Business Scale in Central Java Province

Abstract: The purpose of this research was to analyze factors influencing farmers' decision to increase beef cattle business scale through improved technology. The research was conducted by using a survey method. Five districts were purposively selected in three base areas and two non-base areas of beef cattle in Central Java Province, Indonesia. Twenty beef cattle groups were selected based on the largest cattle population managed and their performance, while 196 respondents were randomly selected. Farmers' decision to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 10 publications
1
10
0
12
Order By: Relevance
“…Whereas, the income average on total cost was as much as IDR.4,867,808.92 per year or IDR 405,650.74 per month smaller than the work minimum wage in Semarang Regency as much as IDR 1,415,000.00 per month. This because farmers are still weak in lending money in the bank for increasing business scale and In a traditional management system, so the goal of cattle business for profit frequently fails to achieve (Roessali et al, 2011). Mukson et al (2010) stated that the dairy cattle in Semarang Regency still faces a number of problems, one of which is limited access to bank loans.…”
Section: The Income Of Daily Cattle Businessmentioning
confidence: 99%
“…Whereas, the income average on total cost was as much as IDR.4,867,808.92 per year or IDR 405,650.74 per month smaller than the work minimum wage in Semarang Regency as much as IDR 1,415,000.00 per month. This because farmers are still weak in lending money in the bank for increasing business scale and In a traditional management system, so the goal of cattle business for profit frequently fails to achieve (Roessali et al, 2011). Mukson et al (2010) stated that the dairy cattle in Semarang Regency still faces a number of problems, one of which is limited access to bank loans.…”
Section: The Income Of Daily Cattle Businessmentioning
confidence: 99%
“…Lebih lanjut dikatakan bahwa skala kepemilikan yang kecil disebabkan terbatasnya kepemilikan modal, ketersediaan tenaga kerja, dan manajemen pemeliharaan. Roessali et al (2011) mengkaji faktor penentu peningkatan skala usaha sapi potong dengan menerapkan model persamaan Tobit. Hasil penelitiannya menyimpulkan bahwa terdapat korelasi positif antara tenaga kerja keluarga serta harapan peningkatan pendapatan terhadap skala usaha sapi potong.…”
Section: Karakteristik Usaha Penggemukan Sapi Potongunclassified
“…While, OR of 1.37 on variable of number of cattle reared was the indication that 1 head increase on cattle raised most likely will increase the opportunity of farmers' courage to expand their business 1.37 times as much. Roessali et al (2011) reported that age of farmers has no significant influence on their willingness to expand their business, while Mukson et al (2010) on contrary reported that age has significant influence on production of milk. According to Soekartawi (1988), older farmers tend to be less courage to adopt and diffuse new technology.…”
Section: Parameter Estimation By Logit Model Regression Analysismentioning
confidence: 98%